Penyuluhan Disiplin Protokol Kesehatan Covid-19 di Desa Lonuo Kecamatan Tilongkabila Kabupaten Bone Bolango Provinsi Gorontalo - Sri Maryati; Nurmuhniyanti M. Hubaib; Gamar Ambarwati DG. Palallo; Nurul Fajriah Ramadhani; Moh. Zulkifli S. Togila; Sitti Annisa Pontoh; Ramli Latif; Fatma D. Abas; Fazli Batadi; Saptan Gobel; Moh. Ramadhan (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
Face-to-face learning implemented by the government raises parents concerns because theCovid-19 pandemic isn't over yet. The purpose of this community service activity is to increase awareness of health and improve health protocol discipline for Covid-19 prevention inLonuo Village, Tilongkabila Sub District, Bone Bolango Regency. The target of this program is elementary school and kindergarten students. The methods used in this community service program are socialization of the Covid-19 disease,health protocol discipline, distribution of masks, hand sanitizers, and leaflets, practicing good and correct hand washing, and coloring pictures by kindergarten and preschool students. The number of participants in this community service is 80 students in Lonuo Village, Tilongkabila Sub District, Bone Bolango Regency. The implementation of this program raised a positive response from teachers, students and the student’s parents. They need information about COVID-19 and life patterns during the pandemic. This program is expected to reduce parental concerns in re-implementing face-to-face learning. This program is expected to provide benefits for schools in increasing student obedience to comply health protocols.